ASSOCIATION BETWEEN TROUBLE SLEEPING AND ORAL CONDITIONS AMONG SCHOOLCHILDREN - Juliana Moro; Pablo Santos; Angela Giacomin; Mariane Cardoso; Michele Bolan (Sociedade de Pediatria de São Paulo, 2020)
ABSTRACT Objective: To investigate the prevalence of self-reported trouble sleeping due to dental problems and its association with oral conditions in schoolchildren. Methods: This is a cross-sectional study carried out with a representative sample of 1,589 schoolchildren aged 8-10 years enrolled in public schools from Florianópolis, Santa Catarina, Brazil. Non-clinical data included a questionnaire about socioeconomic indicators answered by parents/guardians. Children were questioned about whether they had trouble sleeping due to dental problems and about previous history of toothache. Clinical oral examinations were performed to evaluate dental caries - Decayed, Missing, and Filled Teeth Index (DMFT/dmft index) and its clinical consequences [PUFA/pufa index: considering the presence of pulpal involvement (P/p); ulceration of tissues due to tooth fragments from decayed crowns (U/u); fistula (F/f); and abscesses (A/a), and traumatic dental injuries (TDI)]. We conducted a descriptive analysis and used adjusted logistic regression models (p<0.05; 95%CI). Results: The prevalence of trouble sleeping due to dental problems was 28%. Children with untreated dental caries (OR 1.32; 95%CI 1.05-1.67) and clinical consequences from the PUFA/pufa index (OR 1.89; 95%CI 1.45-2.46) had higher chances of reporting trouble sleeping due to dental problems. Conclusions: Approximately one-third of the children declared having trouble sleeping due to dental problems. Untreated dental caries and its clinical consequences were associated with self-reported trouble sleeping due to dental problems in schoolchildren.